2000
DOI: 10.4269/ajtmh.2000.62.663
|View full text |Cite
|
Sign up to set email alerts
|

The influence of zinc supplementation on morbidity due to Plasmodium falciparum: a randomized trial in preschool children in Papua New Guinea.

Abstract: Abstract. Zinc is crucial for normal immune function and can reduce morbidity from multiple infectious diseases. To determine the influence of zinc on malaria morbidity we conducted a randomized placebo-controlled trial of daily zinc supplementation in children residing in a malaria endemic region of Papua New Guinea. A total of 274 preschool children aged 6 to 60 months were given 10 mg elemental zinc (n ϭ 136) or placebo (n ϭ 138) for 6 days a week for 46 weeks. Slide-confirmed malaria episodes were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
3
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 23 publications
1
92
3
6
Order By: Relevance
“…Also there is decrease in the level of plasma Vitamin E 20 and vitamin A 4 during malaria infection. Beneficial protective effects of retinol or zinc on malaria-related morbidity have been documented in Papua New Guinea, Peru and Zanzabari 23,24,25 .In our study there is gradual increase in serum MDA level as the parasitemia increases. Recently D'douza et al 2009 also found the increment in the serum MDA level 26 .…”
Section: Resultssupporting
confidence: 59%
“…Also there is decrease in the level of plasma Vitamin E 20 and vitamin A 4 during malaria infection. Beneficial protective effects of retinol or zinc on malaria-related morbidity have been documented in Papua New Guinea, Peru and Zanzabari 23,24,25 .In our study there is gradual increase in serum MDA level as the parasitemia increases. Recently D'douza et al 2009 also found the increment in the serum MDA level 26 .…”
Section: Resultssupporting
confidence: 59%
“…16 Host nutritional status has generally been considered to be unrelated to the morbidity and mortality of malaria, 22 but new studies are challenging this belief. Community-based trials show that periodic high dose vitamin A supplementation 4 and oral zinc supplementation 23 reduce the morbidity due to P. falciparum malaria in Papua New Guinea. It is not known whether improved carotenoid status, either through dietary intervention or supplementation, will improve clinical outcomes of acute malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency is a serious problem in developing countries. Many studies have shown the adverse effects on growth and morbidity as well as the prevention of infection by zinc supplementation in pregnant women, infants and children (Bates et al, 1993;Goldenberg et al, 1995;Brown et al, 1998;Bhutta et al, 1999;Caulfield et al, 1999;Shankar et al, 2000;Osendarp et al, 2001;Black et al, 2004). Zinc deficiency has also been reported in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%